Poverty in Gombe State: Causes, Manifestations and Strategies of Alleviation - Babayo Sule; Usman Sambo (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Poverty is a phenomenon that is affecting our society negatively as its scorch keeps on biting harder despite the rate in which revenue is rising in Nigeria. Gombe State is one of the states that is categorized among the poorest in Nigeria for a decade. Poverty is affecting the socioeconomic and political wellbeing of Gombe State in many perspectives. This paper examined the issues and perspectives of poverty in Gombe State particularly the causes, manifestations and strategies of alleviation. The work used primary and secondary sources of data collection where some respondents were selected through a simple random sampling for questionnaire administration and other key stakeholders were identified for an in-depth interview. The secondary source involves documents such as books, reports, journals and internet sources. The data obtained were presented and analysed using statistical tools such as tables and charts where applicable. The paper concludes that; poverty is caused mainly due to poor government’s macro and micro economic policies and that poverty level in Gombe State has reached an unbearable index of 74.6 % according to the research and also the National Bureau of Statistics report which ranked the State the third most poor State in the country in 2015. The paper recommends that, for poverty to be alleviated in Gombe State, there should be a comprehensive and integrated approach via well designed policies such as Conditional Cash Transfer, development of agricultural sector, small scale industrialisation and youth empowerment schemes. It is also recommended that some models like Malaysian social investment and empowerment should be considered.